Can Weeds Overtopping Soybean or Adzuki Bean Be Mechanically Pulled to Reduce Their Seed Input?. (14th March 2019) - Simard, Marie-Josée; Page, Eric R.; Nurse, Robert E.
Abstract: Tall weeds escaping early weed management, such as weeds resistant to one or multiple herbicides, are an increasing concern. When weeds reach a certain size, few options other than hand weeding will limit the production and dispersal of seeds. The objective of this project was to evaluate the efficacy of the Bourquin Organic Weed Puller® (a rotating series of wheels that grab and pull) at removing tall weeds before they shed seeds in soybean and adzuki bean. Trials were set up in Canada at the Agriculture and Agri-Food Canada research farms at Saint-Jean-sur-Richelieu (SJR), QC (2 yr), and Harrow (HAR), ON (1 yr), on a loamy and a sandy soil, respectively. The experimental design included crops of different potential heights (different soybean cultivars and adzuki bean), two weed species per location (common lambsquarters [both locations] and common ragweed or redroot pigweed at HAR), and two pulling dates. The set-up also included weedy and herbicide-treated control plots. Weeds overtopping the crop canopy by at least 10 cm were tagged and characterized. Damage from the weed puller was rated as 1, pulled (desired effect); 2, cut; 3, folded; 4, stripped; and 5, intact. The seed production of damaged and intact weeds was also recorded. Less than one-third of common ragweed or redroot pigweed plants were pulled during any treatment combination. The highest pulling rates were observed for common lambsquarters at SJR (43%), but very few were pulled at HAR (3.1% max). Pulling rates were not high enough to potentially control seed inputs from herbicide-resistant populations, and successfully pulled common lambsquarters left on the ground produced thousands of viable seeds.